PENGARUH BEBAN KERJA, STRES KERJA DAN MOTIVASI KERJA TERHADAP KINERJA PERAWAT RUMAH SAKIT ISLAM IBNU SINA PEKANBARU - Aprilia, Friska; Pramadewi, Arwinence; ', Samsir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine the influence of workload, job stress and work motivation on the nurse performance in Ibnu Sina Islamic Hospital Of Pekanbaru. There are 4 variabels in this reserach, Workload (X1), Work Stress (X2), Work Motivation (X3) and Nurse Performance (Y). The population of this study were the nurses in-patient ward totaling 104 nurses. Sampling technique using a proposional random sampling method and the data obtained were analyzed using multiple linear regression using SPSS version 17.0. Based on hypotesis testing that has been done, the result showed that the workload, work stress and work motivation positive and significant impact on nurse performance in Ibnu Sina Islamic Hospital of Pekanbaru. The result of this study showed, simultaneous regression test (f-test) showed that workload, work stress and work motivation simultaneously affect the performance of nurses, while the partial test (t-test) of workload, work stress and work motivation partially inflluence the performance of nurses in Ibnu Sina Islamic Hospital of Pekanbaru. It is recommended to the Hospital to conduct further analysis related to the nurse perception of workload, work stress and work motivation and make appropriate policies in order to improve nurses performance.Keywords: Workload, Work Stress, Work Motivation and Nurses Performance